Implementation of Smoke-Free Area Policy Education as a Medium for Public Health Learning - Sri Ayu Mulianty Sondjaja Putri; Dani Ramdani; Indriyati Kamil (Civiliza Publishing, Indonesia., 2025)
The Smoke-Free Area (KTR) policy not only functions as a regulatory instrument, but also as a means of health education aimed at fostering awareness and healthy living behavior in the community. However, the implementation of the KTR policy in Situraja District, Sumedang Regency, has not been optimal, despite being regulated in Sumedang Regency Regulation Number 17 of 2014. This study aims to analyze the implementation of the KTR policy from a public health education perspective and identify supporting and inhibiting factors as a social learning process. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. Research informants included sub-district officials, village officials, public facility managers, health educators, and the community. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the KTR policy as a health education medium is not optimal, which is characterized by weak educational socialization, limited learning support resources, low commitment of implementers in the educational function, and the lack of development of education-based operational procedures. This condition results in low understanding and internalization of healthy living values ​​in the community. Therefore, it is necessary to strengthen health education strategies, increase human resource capacity, and integrate participatory learning approaches in the implementation of KTR policies to increase the effectiveness of education and the sustainability of healthy community behavior.